Immune Modulation Plus Tumor Ablation: Adjuvants and Antibodies to Prime and Boost Anti-Tumor Immunity In Situ - van den Bijgaart, Renske J. E.; Schuurmans, Fabian; Fütterer, Jurgen J.; Verheij, Marcel; Cornelissen, Lenneke A. M.; Adema, Gosse J. (Frontiers in Immunology, 2021)
In situ tumor ablation techniques, like radiotherapy, cryo- and heat-based thermal ablation are successfully applied in oncology for local destruction of tumor masses. Although diverse in technology and mechanism of inducing cell death, ablative techniques share one key feature: they generate tumor debris which remains in situ. This tumor debris functions as an unbiased source of tumor antigens available to the immune system and has led to the concept of in situ cancer vaccination. Most studies, however, report generally modest tumor-directed immune responses following local tumor ablation as stand-alone treatment. Tumors have evolved mechanisms to create an immunosuppressive tumor microenvironment (TME), parts of which may admix with the antigen depot. Provision of immune stimuli, as well as approaches that counteract the immunosuppressive TME, have shown to be key to boost ablation-induced anti-tumor immunity. Recent advances in protein engineering have yielded novel multifunctional antibody formats. These multifunctional antibodies can provide a combination of distinct effector functions or allow for delivery of immunomodulators specifically to the relevant locations, thereby mitigating potential toxic side effects. This review provides an update on immune activation strategies that have been tested to act in concert with tumor debris to achieve in situ cancer vaccination. We further provide a rationale for multifunctional antibody formats to be applied together with in situ ablation to boost anti-tumor immunity for local and systemic tumor control.